History Of The Development Of Islam In Indonesia - Ririn Shafitri; Muhammad Yandra; Ridwal Trisoni; Muhammad Yahya (Journal of Paddisengeng Technology, 2025)
Background. The history of the development of Islam in Indonesia is a crucial study for understanding the social, cultural, and political processes that have shaped Indonesian society to this day. The arrival and development of Islam did not occur in a single instance, but rather through various channels and interactions with local cultures. Therefore, a comprehensive understanding of the dynamics of Islamic history in Indonesia is necessary to understand its contribution to the formation of national identity. Purpose. This study aims to examine the historical development of Islam in Indonesia from its early days to the modern period. Specifically, it analyzes theories about the arrival of Islam, the channels through which it spread, the role of Islamic figures and institutions, and the impact of Islam on the social, cultural, and political life of Indonesian society. Method. This research employed a qualitative method with a library research approach. Data were obtained from history books, scientific journals, and relevant academic sources discussing the development of Islam in Indonesia. The data were analyzed using a historiographic approach, emphasizing descriptive and interpretive analysis. Results. The study shows that Islam spread peacefully in Indonesia through trade, education, marriage, and cultural outreach. The process of Islamization occurred gradually and adapted to local culture, giving rise to a moderate and inclusive form of Islam. Furthermore, Islam played a significant role in shaping social structures, religious traditions, and the development of education and politics in Indonesia to the present day. Conclusion. Based on a study of the history of Islam's development in Indonesia, it can be concluded that the entry and development of Islam occurred gradually, peacefully, and adaptively through various channels such as trade, education, marriage, and cultural propagation. These findings indicate that the success of Islamization in Indonesia is inseparable from Islam's ability to interact with local cultures without losing its teachings. This study's contribution to science lies in strengthening the historiographical understanding of the moderate, inclusive, and contextual character of Indonesian Islam. This study's limitations are the use of data sourced from library research, which therefore does not delve deeply into empirical field data and specific regional differences, which could provide opportunities for further research.